Structural Anthropology In America And France: A Comparison - Heddy Shri Ahimsa Putra Putra (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2003)
More than fifty years have passed since Claude Lévi-Strauss, the father ofFrench structural anthropology, applied structural analysis and built modelsto elucidate orders beneath various kin-ship systems, in his monumental work The Elementary Structures of Kinship, and more than twenty years have passed since another structural analysis appeared in Americananthropology. However, such important theoretical developments seemed to have no serious impacts on social sciences and human studies in Indonesia. Only very small number of articles using structural paradigmhave been published in the last few years (Ahimsa-Putra, 1995; 1997; 1998; 1999a; 1999b; 2000; 2001), and there seemed to be no serious reactions -in the form of comments, critiques or discussions- from Indonesian social scientists on this paradigm1. This, I think, reflects thestagnancy of the social and cultural sciences in Indonesia such as anthropology, archeology, history, linguistics, literature and sociology), which unfortunately have never really managed to give any significantcontribution to the theoretical developments in their own fields after their establishment in Indonesian universities forty or so years ago.